An adversarial ethics for campaigns and elections - Bagg, S; Tranvik, I (Cambridge University Press, 2019)
Existing approaches to campaign ethics fail to adequately account for the “arms races” incited by competitive incentives in the absence of effective sanctions for destructive behaviors. By recommending scrupulous devotion to unenforceable norms of honesty, these approaches require ethical candidates either to quit or lose. To better understand the complex dilemmas faced by candidates, therefore, we turn first to the tradition of “adversarial ethics,” which aims to enable ethical participants to compete while preventing the most destructive excesses of competition. As we demonstrate, however, elections present even more difficult challenges than other adversarial contexts, because no centralized regulation is available to halt potential arms races. Turning next to recent scholarship on populism and partisanship, we articulate an alternative framework for campaign ethics, which allows candidates greater room to maneuver in their appeals to democratic populations while nevertheless requiring adherence to norms of social and political pluralism.